Analisis Kebijakan Reward dan Punishment terhadap Peningkatan Kedisiplinan Siswa di SMP Islam Asshiddiq Bone - Alif Alwaidin; Feny Wanda Waguna; Reisya Maharani; Arifah Lailatul Hikmah (Institusi Agama Islam Negeri (IAIN) Bone, 2025)
This study looks at how reward and punishment policies help improve student behavior at SMP Islam Asshiddiq Bone. Good behavior plays a big role in how teaching and learning happens, and using rewards and punishments is meant to help students take responsibility for following school rules. The research uses a descriptive qualitative method, collecting data through interviews, observations, and document reviews. The findings show that rewards like the “Best of Student” program and merit stars work well in encouraging students to behave properly. Punishments are given step by step, starting with warnings and then involving parents, and they are designed to teach students instead of using physical punishment. The policies are checked regularly through weekly meetings and daily discussions among teachers. This method has been effective, as seen by fewer rule-breaking incidents and more understanding from students about the effects of their actions. Issues like differences in characters between teachers and students are handled through close teamwork and individual attention. In the end, the success of the reward and punishment system depends a lot on how consistently it is used and the support from teachers, counselors, parents, and the whole school community.